2021
DOI: 10.12688/f1000research.24818.3
|View full text |Cite
|
Sign up to set email alerts
|

β-lactamases (bla TEM, bla SHV, bla CTXM-1, bla VEB, bla OXA-1) and class C β-lactamases gene frequency in Pseudomonas aeruginosa isolated from various clinical specimens in Khartoum State, Sudan: a cross sectional study

Abstract: Background: Pseudomonas aeruginosa is a pathogenic bacterium, causing nosocomial infections with  intrinsic and acquired resistance mechanisms to a large group of antibiotics, including β-lactams. This study aimed to determine the susceptibility pattern to selected antibiotics and to index the first reported β-lactamases genes frequency in Ps. aeruginosa in Khartoum State, Sudan. Methods: 121 Ps. aeruginosa clinical isolates from various clinical specimens were used in this cross sectional study conducted in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
6
1
1
Order By: Relevance
“…A high prevalence of bla CTX-M gene was also found in studies conducted by Maleki et al (92%) and Founou et al (100%) (34,35). In contrast with our study, the study by Abdelrahman et al only found 32.6% bla CTX-M producer isolates (15). The frequency of bla AMP-C and bla SHV genes in our study was higher than that reported in a previous study by Abdelrahman et al in Sudan (15).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A high prevalence of bla CTX-M gene was also found in studies conducted by Maleki et al (92%) and Founou et al (100%) (34,35). In contrast with our study, the study by Abdelrahman et al only found 32.6% bla CTX-M producer isolates (15). The frequency of bla AMP-C and bla SHV genes in our study was higher than that reported in a previous study by Abdelrahman et al in Sudan (15).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our study, the study by Abdelrahman et al only found 32.6% bla CTX-M producer isolates (15). The frequency of bla AMP-C and bla SHV genes in our study was higher than that reported in a previous study by Abdelrahman et al in Sudan (15). In a study conducted in Egypt, 50% of isolates were positive for bla TEM gene, which was consistent with our study results (36).…”
Section: Discussionsupporting
confidence: 84%
“…is resistance is mainly associated to point mutations in gyrA (encoding GyrA subunit of DNA gyrase) and parC (encoding parC subunit of topoisomerase IV) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas aeruginosa strains that are difficult to treat, such as multidrug-resistant (MDR) and extensively drug-resistant (XDR), have risen to become the leading cause of nosocomial infection in humans and pose a life-threatening threat to immunocompromised patients in health care settings [ 1 4 ]. In spite of the fact that limiting-dose of antibiotics given in bits may strengthen sensitive bacteria and transformed them into resistant versions, the other imperative factors such as bacterial genomic mutations and acquisition of resistance genes, particularly those encoding extended-spectrum β-lactamases (ESBL) or carbapenemases through horizontal gene transfer, are also attributed to acquired resistance [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%